α-Synuclein and Mitochondria: Partners in Crime? - Nakamura, Ken (Springer US, 2013)
Increased α-synuclein levels and mutations in mitochondria-associated proteins both cause familial Parkinson’s disease (PD), and synuclein and mitochondria also play central, but poorly understood, roles in the pathogenesis of idiopathic PD. A fraction of synuclein interacts with mitochondria, and synuclein can produce mitochondrial fragmentation and impair mitochondrial complex I activity. However, the consequences of these mitochondrial changes for bioenergetic and other mitochondrial functions remain poorly defined, as does the role of synuclein–mitochondria interactions in the normal and pathologic effects of synuclein. Understanding the functional consequences of synuclein’s interactions with mitochondria is likely to provide important insights into disease pathophysiology, and may also reveal therapeutic strategies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13311-013-0182-9) contains supplementary material, which is available to authorized users.